2003
DOI: 10.1038/nature01870
|View full text |Cite
|
Sign up to set email alerts
|

A camelid antibody fragment inhibits the formation of amyloid fibrils by human lysozyme

Abstract: experiments in Fig. 5, the cultured microglia (see Supplementary Figure) that had been preincubated with or without ATP (50 mM) were injected intrathecally in normal rats (see Supplementary Methods for full details). ImmunohistochemistryTransverse L5 spinal cord sections (30 mm) were cut and processed for immunohistochemistry with anti-P2X4R antibody (Alomone). Identification of the type of P2X 4 R-positive cells was performed with the following markers: for microglia, OX42 (Chemicon) and iba1 (a gift from S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
275
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 225 publications
(287 citation statements)
references
References 29 publications
(32 reference statements)
9
275
3
Order By: Relevance
“…In order to carry out detailed studies of such processes in vitro, it is therefore necessary to increase considerably the rates at which they occur. For globular proteins, one way of achieving this objective is to employ conditions that favour the formation of at least partially unfolded states, for example low pH values [25], high temperatures [26], low to moderate concentrations of strong denaturants [27,28], or the presence of organic solvents [13,29]. Second, the structural characterisation of the various species formed during the process of fibril formation is complicated by their heterogeneity and by their transient or insoluble nature.…”
Section: The Generic Nature Of the Amyloid Structurementioning
confidence: 99%
See 3 more Smart Citations
“…In order to carry out detailed studies of such processes in vitro, it is therefore necessary to increase considerably the rates at which they occur. For globular proteins, one way of achieving this objective is to employ conditions that favour the formation of at least partially unfolded states, for example low pH values [25], high temperatures [26], low to moderate concentrations of strong denaturants [27,28], or the presence of organic solvents [13,29]. Second, the structural characterisation of the various species formed during the process of fibril formation is complicated by their heterogeneity and by their transient or insoluble nature.…”
Section: The Generic Nature Of the Amyloid Structurementioning
confidence: 99%
“…Antibodies could mediate their inhibitory effect by directly binding to the regions of a peptide or a protein where the conformational changes or the aggregation processes are initiated [64,74]. It has been shown, however, that they can also act through a more subtle mechanism [28]. Thus, we have recently reported that a single-domain fragment of a camelid antibody (V H H) raised against wild type human lysozyme inhibits the in vitro aggregation of its amyloidogenic variant, D67H (Fig.…”
Section: Elucidation Of Misfolding Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that nanobodies exhibit a high stability is especially important for their use as molecular probes to study the process of amyloid fibril formation because denaturing conditions and/or long incubation time (up to several weeks) need generally to be used to trigger the in vitro aggregation of target proteins. Finally, their high stability allows most of nanobodies to be easily concentrated to 1e15 mg mL À1 in standard buffers [46] and to be freeze-dried without losing their functionality [37,69].…”
Section: Nanobodies Are Highly Stable Entitiesmentioning
confidence: 99%